2010
DOI: 10.1111/j.1365-2761.2010.01142.x
|View full text |Cite
|
Sign up to set email alerts
|

First description of atypical furunculosis in freshwater farmed Atlantic salmon, Salmo salar L., in Chile

Abstract: We report the first isolation, identification and characterization of a group of Chilean strains of atypical Aeromonas salmonicida isolated from freshwater farmed Atlantic salmon, Salmo salar. Affected fish showed superficial ulcers and pale liver with or without petechial haemorrhages. Outbreaks of the disease occurred in two farms in the south of Chile about 2200 km apart. Five strains were isolated in pure culture and identified by serological assays and immunofluorescence tests as belonging to Aeromonas sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…The mentioned systems normally tend to identify all Aeromonas strains as A. hydrophila (Figueras, 2005;Soler et al, 2003b). Some other authors have also reported poor results from the API systems and discrepancies with traditional tube testing when identifying Aeromonas strains isolated from fish (Godoy et al, 2010;Han et al, 2011;Joseph & Carnahan, 1994;and references therein). Some methods may even misidentify Aeromonas strains as Vibrio species (Park et al, 2003;Soler et al, 2003b).…”
Section: Phenotypic Identification With Conventional Methods and Minimentioning
confidence: 99%
See 4 more Smart Citations
“…The mentioned systems normally tend to identify all Aeromonas strains as A. hydrophila (Figueras, 2005;Soler et al, 2003b). Some other authors have also reported poor results from the API systems and discrepancies with traditional tube testing when identifying Aeromonas strains isolated from fish (Godoy et al, 2010;Han et al, 2011;Joseph & Carnahan, 1994;and references therein). Some methods may even misidentify Aeromonas strains as Vibrio species (Park et al, 2003;Soler et al, 2003b).…”
Section: Phenotypic Identification With Conventional Methods and Minimentioning
confidence: 99%
“…salmonicida the similarity was 99.85%. In our view Godoy et al (2010) forgot to consider that the species A. bestiarum shows an identical 16S rRNA gene sequence to A. salmonicida subsp. achromogenes and A. salmonicida subsp.…”
Section: Application or Comparative Evaluation Of The Described Pcr Mmentioning
confidence: 98%
See 3 more Smart Citations